Brianna E. Robertson-Kirkland, Venanzio Rauzzini and the Birth of a New Style in English Singing: Scandalous Lessons (New York and Abingdon: Routledge, 2022). ISBN: 978-1-032-20029-3, 244pp, £39.99 (paperback). - Talbot, Rachel (Journal of the Society for Musicology in Ireland, 2024)
A Review of Brianna E. Robertson-Kirkland, Venanzio Rauzzini and the Birth of a New Style in English Singing: Scandalous Lessons (New York and Abingdon: Routledge, 2022). ISBN: 978-1-032-20029-3, 244pp, £39.99 (paperback).